2021
DOI: 10.1108/sampj-07-2020-0259
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability strategy of Indonesian and Malaysian palm oil industry: a qualitative analysis

Abstract: Purpose Global palm oil production is growing rapidly, especially in Southeast Asia, with Indonesia and Malaysia as the biggest producers. Despite significant contributions to these countries’ economies, environmental and social aspects continue to be debated within this industry. The sustainability strategy is very important for the palm oil industry. This study aims to explore the sustainability strategy using six elements, namely, stakeholder engagement, governance and leadership, sustainability view and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…Riau Province must establish and reflect as a representative of government agencies dealing with mature palm oil. An institution's maturity will also be reflected in things such as the strength of the policy, how large and often the effect of the process produces an outcome, policy, and even a strategy in reading more broadly and in the future (Wardhani & Rahadian, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Riau Province must establish and reflect as a representative of government agencies dealing with mature palm oil. An institution's maturity will also be reflected in things such as the strength of the policy, how large and often the effect of the process produces an outcome, policy, and even a strategy in reading more broadly and in the future (Wardhani & Rahadian, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Are the economic benefits commensurate with the environmental damage caused? Sustainability of implementation strategies from strong leaders and strengthening among stakeholders (Wardhani & Rahadian, 2021). The existence of an economy that is not accompanied by a strengthening of the environment is something that is not sustainable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste disclosure data come from the sustainability report 2020 of non-financial public companies that are listed in the stock market of Indonesia. Sustainability reports are one of the media that are often used by companies in informing their sustainability strategies [20]. Availability and access to data are the reasons behind the use of secondary data.…”
Section: Methodsmentioning
confidence: 99%
“…However, a cointegration analysis from 2018 to 2050 reported that rainfall changes affect future and spot prices with different time lags [60]. Furthermore, a study utilised monthly temperature anomalies to successfully predict palm oil yields [61].…”
Section: Factors Affecting Palm Oil Growth and Qualitymentioning
confidence: 99%